¡Fuera yanquis de Puerto Rico! (Comisión Latinoamericana de la Unión Internacional de Estudiantes, 1971)
Facsimile of bulletin; headline photo of man graffiting wall with political slogan Facsimile of bulletin 'Noticias para América Latina', n.73, year IV, 6 April, 1971 PO-1360